Analisis Nilai Pendidikan Karakter dalam Kumpulan Cerpen Kompas Id Edisi Bulan Maret 2024 - Roziqqi, Awalul; Novitasari, Lusy; Munifah, Siti (LEKSIS: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
Understanding literary works in relation to the real world and social aspects of society is known as the sociological approach to literature. This research aims to describe the values of character education and find out or reveal the function of these character education values in social life in the collection of short stories in the daily Kompas.id March 2024 edition. This research was conducted using qualitative descriptive methods. Analyzed using a qualitative literature review approach. The data analysis technique uses the Miles and Hubberman technique which consists of data reduction, data presentation and drawing conclusions. The results of the research show that the collection of short stories in the March 2024 edition of the daily Kompas.id contains character education values. Includes: the value of hard work character education, religious character education, creative values, honest values, curiosity values, social care values, hard work values, environmental care values,friendly values, and responsibility values.